2014
DOI: 10.1155/2014/726179
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofβ-Lactamases and Outer Membrane Porins amongKlebsiella pneumoniaeStrains Isolated in Iran

Abstract: This descriptive study was accomplished on 83 K. pneumoniae strains isolated from two hospitals in Tehran, Iran. Antibiotic susceptibility tests were performed by disc diffusion and broth microdilution methods. ESBLs, MBL, Amp-C, and KPC producing strains were detected by phenotypic confirmatory test, combination disk diffusion test (CDDT), Amp-C detection kit, and modified Hodge test, respectively. OXA-48, NDM-1, and CTX-M-15 genes were detected by PCR and sequencing methods. The outer membrane porins such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
(25 reference statements)
4
11
1
Order By: Relevance
“…These results were similar to previous studies by Hashemi et al [28], Ma et al [29], Ruiz [30] and Findlay et al [31] who also reported defects in OmpK35 and/or OmpK36 production in CR-KP isolates.…”
Section: Discussionsupporting
confidence: 92%
“…These results were similar to previous studies by Hashemi et al [28], Ma et al [29], Ruiz [30] and Findlay et al [31] who also reported defects in OmpK35 and/or OmpK36 production in CR-KP isolates.…”
Section: Discussionsupporting
confidence: 92%
“…The first report of OXA-48producing K. pneumoniae strains in Iran was presented by Azimi et al [27]. In two separate studies conducted in Tehran hospitals (capital of Iran), the prevalence of bla OXA-48 among CRKP isolates was reported as 96.4% [27] and 4.1% [28]. Another study in southwestern Iran showed that 6.9% of CRKP isolates were positive for bla OXA-48 [29].…”
Section: Discussionmentioning
confidence: 99%
“…OmpK and carO genes that regulate expression of mutated efflux pump were detected in Hashemi et al and Pajand et al studies, respectively. 83 , 93 In another study, efflux pump’s activity and mutations in porins were investigated. 112 These results can expand the view about true mechanisms of resistance to carbapenems in developing countries.…”
Section: Discussionmentioning
confidence: 99%